Pricing indefinitely lived assets: Experimental evidence - John Duffy; Janet Hua Jiang; Huan Xie (Bank of Canada, 2023)
We study indefinitely lived assets in experimental markets and find that the traded prices of these assets are, on average, about 40% of the risk-neutral fundamental value. Neither uncertainty about the value of total dividend payments nor horizon uncertainty about the duration of trade can account for this low traded price. An Epstein and Zin (1989) recursive preference specification that models the dynamic realization of dividend payments and incorporates risk preferences can rationalize the low traded price observed in our indefinitely lived asset market.
Keywords: C91; C92; D81; G12; 330; Asset pricing; Financial markets